Predicting Perinatal Outcomes in Fetuses with Congenital Diaphragmatic Hernia Using Ultrasound and Magnetic Resonance Imaging. Issue 4 (25th October 2021) - Huang, Jun; Liu, Hongli; Hu, Haiyan; Zhang, Li; Cai, Ping; Li, Yonggang; Li, Junnan
Abstract : Abstract: Congenital diaphragmatic hernia is a congenital fetal disease, which mainly causes pulmonary hypoplasia and pulmonary hypertension. Effective early prenatal diagnosis can detect and predict the prognosis of congenital diaphragmatic hernia in infants, thus provide a reference for prenatal counseling, early intervention, and potential choices for the child's family. Ultrasound and magnetic resonance imaging are the most commonly used methods for non-invasive examination of the fetus. This paper discusses evaluation parameters based on these two imaging modalities.